Sitagliptin ameliorates kidney lesions in a rat model of type 2 diabetes due to anti-inflammatory and anti-apoptotic effects - Marques, C. (2015)
Objective: This study aimed to evaluate the efficacy of sitagliptin, a dipeptidyl peptidase IV (DPP-IV) inhibitor, in preventing the deleterious effects of diabetes on the kidney in an animal model of T2DM, the Zucker Diabetic Fatty (ZDF) rat. Methods: ZDF rats (aged 20 weeks) were treated with sitagliptin (10 mg/kg bw/day) during 6 weeks. Glycaemia, HbA1c, urea and creatinine levels were monitored. Kidney glomerular and tubulointerstitial lesions were assessed using a semiquantitative rating. Kidney mRNA and/or protein content of DPP-IV, GLP-1, TNF-α, IL-1β, BAX, Bcl-2 and Bid were evaluated by RT-PCR and/or WB. Protein distribution was evaluated by immunohistochemistry. Results: Sitagliptin treatment improved glycaemic control, as reflected by the significantly reduced levels of glycaemia and HbA1c, and prevented the diabetes-induced increase in DPP-IV levels and decrease in GLP-1 levels. Sitagliptin ameliorated diabetes-induced glomerular atrophy and IFTA, and the increased urea levels. Sitagliptin decreased kidney IL-1β and TNF-α, and prevented the increase of BAX/Bcl-2 ratio and Bid protein levels, which indicates protective effects against inflammation and pro-apoptotic state in the kidney of diabetic rats, respectively. Conclusion: Sitagliptin might have a major role in preventing diabetic nephropathy evolution due to anti-inflammatory and anti-apoptotic properties.